2020
DOI: 10.1002/jbmr.4712
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol-Dependent and -Independent Regulation of Intestinal Calcium Absorption, Osteoblast Function, and Skeletal Mineralization during Lactation and Recovery in Mice

Abstract: Recovery from lactation-induced bone loss appears to be calcitriol-independent, since mice lacking 1-alpha-hydroxylase or vitamin D receptor (VDR) exhibit full skeletal recovery. However, in those studies mice consumed a calcium-, phosphorus-, and lactose-enriched "rescue" diet. Here we assessed whether postweaning skeletal recovery of Vdr null mice required that rescue diet. Wild type (WT) and Vdr null mice were raised on the rescue diet and switched to a normal (1% calcium) diet at Day 21 of lactation until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Furthermore, calcitriol contributes to calcium salt replenishment, new bone formation, increased calcium and phosphorus reabsorption by renal tubular cells, and reduced urinary excretion [26]. A pivotal target of calcitriol is osteoblasts, in which it prompts the synthesis of matrix and proteins, playing a critical role in bone mineralization, function and metabolism [27][28][29]. Importantly, calcium supplementation alone is insufficient to address bone loss and treat OP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, calcitriol contributes to calcium salt replenishment, new bone formation, increased calcium and phosphorus reabsorption by renal tubular cells, and reduced urinary excretion [26]. A pivotal target of calcitriol is osteoblasts, in which it prompts the synthesis of matrix and proteins, playing a critical role in bone mineralization, function and metabolism [27][28][29]. Importantly, calcium supplementation alone is insufficient to address bone loss and treat OP.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, data obtained from mice have suggested that osteoblasts are potently stimulated to produce osteoid and that calcitriol and/or a calcium-enriched diet are needed for this immature bone to become mineralized. [13][14][15] Pregnancy and lactation are major challenging periods for maternal bone metabolism. However, the female skeleton is well prepared to face these periods successfully, and resistance does not seem to be affected in the long term.…”
Section: Physiology During Lactationmentioning
confidence: 99%
“…Locations for generating calcitriolintracellularly, in peripheral target cells-need to be considered regarding its mechanisms and efficacy for prevention and using vitamin D as an adjunctive therapy [41,42]. The circulating hormonal form of calcitriol generated in renal tubular cells is crucial for musculoskeletal activities and calcium/magnesium metabolism [43,44]. However, calcitriol circulates in the blood in picomolar concentration: it does not enter extra-renal target cells, like immune cells [45,46], to affect their biology and physiological functions [47,48].…”
Section: Vitamin D Deficiency As An Explanation For Susceptibility To...mentioning
confidence: 99%